2013
DOI: 10.1007/s00122-013-2214-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-line cross QTL mapping for biomass yield and plant height in triticale (× Triticosecale Wittmack)

Abstract: QTL mapping in multiple families identifies trait-specific and pleiotropic QTL for biomass yield and plant height in triticale. Triticale shows a broad genetic variation for biomass yield which is of interest for a range of purposes, including bioenergy. Plant height is a major contributor to biomass yield and in this study, we investigated the genetic architecture underlying biomass yield and plant height by multiple-line cross QTL mapping. We employed 647 doubled haploid lines from four mapping populations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 54 publications
5
51
0
1
Order By: Relevance
“…Plant height is a complex trait determined by many genes with small effects (Alheit et al, 2014). Therefore, many QTLs have been mapped on all seven chromosomes using different types of molecular markers, such as SSRs (Inostroza et al, 2009), DArT (Wang et al, 2014) and SNPs (Zhou, Zhang, Zhang, Tan, & Li, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Plant height is a complex trait determined by many genes with small effects (Alheit et al, 2014). Therefore, many QTLs have been mapped on all seven chromosomes using different types of molecular markers, such as SSRs (Inostroza et al, 2009), DArT (Wang et al, 2014) and SNPs (Zhou, Zhang, Zhang, Tan, & Li, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The applications of time-of-flight based sensors are commonly used for evaluating physical/morphological plant characteristics such as plant growth, height, and canopy volume/vigor. These parameters are important in evaluating plant performances during breeding, and can be indicative of yield potential (Wei et al, 2010;Ilker et al, 2013;Alheit et al, 2014;Njogu et al, 2014). In regard to the spectroscopic and imaging techniques, a number of plant phenotypes such as disease susceptibility, susceptibility to drought stress, chlorophyll content, nutrient concentrations, growth rates, and yield potential can be evaluated (Zhang and Kovacs, 2012).…”
Section: Sensor Integration With Small Uavsmentioning
confidence: 97%
“…The semi-dwarf Reduced height ( Rht ) -1 homeologous loci from wheat are located on the group 4 chromosomes of the different genomes (Wilhelm et al 2013). In the mapping population underlying this study, the major plant height gene Ddw1 (Korzun et al 1996; Börner et al 1999), located on the rye chromosome 5R has been shown to segregate and to exhibit a strong effect on plant height (Alheit et al 2014). Photoperiod ( Ppd ) homeologs are located on group 2 chromosomes and in wheat Ppd-D1 has been shown to possess the strongest effect on photoperiod insensitivity and thus the transition from vegetative to generative growth (Beales et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The other identified major QTL do not appear to correspond to any of the abovementioned major genes and therefore may represent other pathways affecting plant development. We have previously performed a QTL mapping in this population for plant height (Alheit et al 2014) and 9 of the 12 plant height QTL regions were identified in this study to affect developmental stage. Although these QTL were not major QTL, this finding illustrates the interrelations between plant height and adult plant development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation